Evolution of the social classes’ structure in Colombia, 1938-2010. Have the middle classes grown? - Fresneda Bautista, Oscar (Sociedad y Economía, 2017)
The article describes the change in the worker social class structure in Colombia between 1938 and 2010 and states the correspondence between this process and the regimes of accumulation that has taken the country in this course. For this purpose uses its own classification that is applied to various statistical sources. It is concluded that in a long-term perspective, after a significant increase in the middle classes during the import substitution regime, not there has been a continuous increase of this classes since the nineties of the twentieth century.